Delivery mode and pelvic organ prolapse: a retrospective observational study. (5th October 2015) - Trutnovsky, G; Kamisan Atan, I; Martin, A; Dietz, HP
Abstract : Objective: To analyse the associations between delivery mode and symptoms and signs of pelvic organ prolapse (POP) in a cohort of symptomatic women. Design: Retrospective observational study. Population: A total of 1258 consecutive women attending a tertiary urogynaecological unit for the investigation of lower urinary tract or pelvic floor disorders between January 2012 and December 2014. Methods: Obstetric history and clinical examination data were obtained from the unit database. Prolapse quantification on imaging was performed using stored four‐dimensional translabial ultrasound volume data sets. Women were grouped into four groups according to the most traumatic delivery reported. The presence of symptoms and signs of POP were compared between delivery groups while controlling for potential confounders. Main outcome measures: Prolapse symptoms, visual analogue score for prolapse bother, International Continence Society Prolapse Quantification System findings and ultrasound findings of anterior, central and posterior compartment descent. Results: Nulliparae showed the lowest prevalence of most measures of POP, followed by women exclusively delivered by caesarean section. Highest prevalences were consistently found in women delivered at least once by forceps, although the differences between this group and women delivered by normal vaginal delivery and/or vacuum extraction were significant in three out of eight measures only. Compared with women in the caesarean section group, the adjusted odds ratios for reporting symptoms of prolapse were 2.4 (95% CI 1.30–4.59) and 3.2 (95% CI 1.65–6.12) in the normal vaginal delivery/vacuum extraction group and forceps group, respectively. Conclusions: There is a clear link between vaginal delivery and symptoms and signs of pelvic organ prolapse in urogynaecological patients. Tweetable abstract: Compared with caesarean section a history of vaginal delivery more than doubles the risk for POP. Tweetable abstract: Compared with caesarean section a history of vaginal delivery more than doubles the risk for POP.